The Effect of Physical Exercises on The Development of Some Physical Fitness for Young Female Basketball Players (3on3) - Safaa, Haneen; Abdulla, Lekaa (Journal of Physical Education, 2023)
The research aimed to prepare a training program to develop speed endurance, agility, and explosive power for young female basketball players (3×3). The experimental approach was used with experimental and control groups design. The subject was young female players in the Dream Academy in Sulaymaniyah Governorate - Iraq, as an experimental group, and the North Gas Club as a control group. Each group contains (6) players. The mean of height, weight, age, and training age was (170.41 ± 4.42 cm) (58.98 ± 2.28 kg) (15.96 ± 0.81 years) (7.25 ± 0.75 years), respectively. Two pilot studies were conducted, the first for confirming the tests’ scientific conditions, and the second for applying for the training program. The pre and post-test have been applied. The training program last for (10) weeks, with (4) training units per week. The statistical package (SPSS V26) was applied for obtaining the results. The study concluded that the application of the training program led to a significant development in speed endurance, agility, and explosive power for the upper limb. It is essential to focus on interactive exercises to develop the physical fitness of basketball players (3on3), as well as focusing on interactive exercises in training tactical skills Which enables the coach to develop physical fitness.